2020
DOI: 10.1108/jfmpc-06-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into BIM uptake among contracting firms: an empirical study in Nigeria

Abstract: Purpose Building information modeling (BIM) is vital in the performance improvement of contracting firms. Thus, there is a need to stimulate its implementation in the construction sector with a view to meeting the competitive demands of the industry. However, there have been very few studies on BIM implementation among contracting firms in Nigeria. Hence, this study aims to examine the current BIM uptake among Nigerian contracting firms, assess the barriers to BIM implementation and examine the ways of improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
“…The availability of studies on BIM and lack of knowledge has also been considered a critical factor to adopting BIM [37]. Other studies in Nigeria looking at contractor firms concluded that cost of the hardware and BIM software, cost of BIM training, and cost of BIM specialists and additional staff recruitment were the primary challenges to BIM adoption [38].…”
Section: Bim Barriersmentioning
confidence: 99%
“…Moreover, some data analysis techniques, such as factor analysis, demands a sufficient sample size which can be effectively obtained using a questionnaire survey (Pallant, 2010). Other construction management studies have also used a similar approach when developing surveys (Marefat et al , 2019; Babatunde et al (2020; Liao and Teo (2017).…”
Section: Methodsmentioning
confidence: 99%
“…In the UK, BIM is mandatory in public projects since 2016 (Aibinu and Venkatesh, 2014). In Finland, all designs must be provided with Industry Foundation Class format as of 2007 (Babatunde et al , 2020). However, middle-income economies, such as China and India, have a lower implementation rate, with India standing among the lowest at 10%–18% (Ahuja et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation